Beyond rest and quiescence (endodormancy and ecodormancy): A novel model for quantifying plant–environment interaction in bud dormancy release. (13th November 2019) - Lundell, Robin; Hänninen, Heikki; Saarinen, Timo; Åström, Helena; Zhang, Rui
Abstract: Bud dormancy of plants has traditionally been explained either by physiological growth arresting conditions in the bud or by unfavourable environmental conditions, such as non‐growth‐promoting low air temperatures. This conceptual dichotomy has provided the framework also for developing process‐based plant phenology models. Here, we propose a novel model that in addition to covering the classical dichotomy as a special case also allows the quantification of an interaction of physiological and environmental factors. According to this plant–environment interaction suggested conceptually decades ago, rather than being unambiguous, the concept of "non‐growth‐promoting low air temperature" depends on the dormancy status of the plant. We parameterized the model with experimental results of growth onset for seven boreal plant species and found that based on the strength of the interaction, the species can be classified into three dormancy types, only one of which represents the traditional dichotomy. We also tested the model with four species in an independent experiment. Our study suggests that interaction of environmental and physiological factors may be involved in many such phenomena that have until now been considered simply as plant traits without any considerations of effects of the environmental factors. Abstract : A novel process‐based plant phenology model is introduced. Unlike the previous models, the model facilitates studying the interaction of physiological and environmental factors in bud dormancy release.